ANALISIS KESEDIAAN MEMBAYAR PENGUNJUNG TERHADAP PAKET WISATA PENDIDIKAN LINGKUNGAN DI TAMAN WISATA ALAM WIRA GARDEN KOTA BANDAR LAMPUNG - Puspita Octaria; Sri Mulatsih; Meti Ekayani (Graduate School Bogor Agricultural University (SPs IPB), 2017)
Lampung is province in Indonesia which is trying to generate income through tourism sectors. One of them is Wira Garden Nature Park (TWA). Wira Garden is located in Bandar Lampung. Activities from tourist increasly effects increase garbage that impact on aesthetics and environmental quality in Wira Garden. So that, takes antourism program based on environmental education. That is able to educate visitors so visitors will participated in activities that aim to promote concern in environment, especially nature tourism. Focus of planning an tourism program based on environmental education is creating environmental education packages, by two activities are planting trees and deposit garbage (deposit refund). Manager of Wira Garden collaborate with BSCH (Bank Sampah Cangkir Hijau) to build garbage deposit program (deposit refund). Environmental education programs in Wira Garden is realized into three types options that are (Personal Green), (Garden Family) and (Jungle Community). Funding for this program is expected from income of (WTP) Willingness to Pay from visitors in Wira Garden.